Políticas de Créditos y Cobranza del Comercial "Agro Fortaleza" en la ciudad de Babahoyo en el periodo 2022. - Cadena Trujillo, Dustin Magredy (2023)
Credit and collection policies have become an essential management tool for businesses, companies or organizations, which is why their development and application must adapt according to the needs of each entity. However, there are businesses that do not have this type of internal policies and tend to have difficulties with the accounts receivable area, this being the main affected. This report consists of "Credit and Collection Policies of the "Agro Fortaleza" Commercial in the city of Babahoyo in the period 2022", it is a store dedicated to the marketing of wholesale sales of chemical products that makes sales on credit and at counted, during the last year (2022) it has had problems in the collection of sales previously made, and with this, its accounts receivable have increased in a worrying manner, this problem arises from the little control and organization that has been given to credit sales, because the necessary parameters or requirements do not apply, therefore, the objective of the report is to verify the existence of a regulation of credit and collection policies in the commercial. The methodology applied was the qualitative method of documentary research, and an interview was applied to the person in charge of the entity with the purpose of obtaining information that allows the preparation of the report, through this the appropriate conclusions and recommendations could be formulated.